Integrating Gender and Social Dimensions into Energy Interventions in Afghanistan - Angelou, Nicolina; Roy, Sanjukta (World Bank, Washington, DC, 2020)
This policy brief suggests ways for Afghanistan to integrate gender and social aspects into energy projects, to better address the country’s energy challenges and enhance its development impact. The energy sector increasingly recognizes that men and women experience different levels of access to benefits and exposure to risks and that these are important elements to be considered for effective policy-making and project design. Women and men have different roles, responsibilities, and voice within households, markets, and their communities. Despite significant improvements, gender equality remains a major challenge in Afghan society, with women and girls being far more disadvantaged than men and boys. Rural grid electrification interventions that involve men and women into project implementation can lead to increased electricity access and use. Energy efficiency measures that specifically target men and women can improve adoption rates and drive behavior change. This policy brief presented a series of actions embedded into energy interventions aiming to address Afghanistan’s energy challenges and improve gender equality. Four types of energy interventions were selected: grid and off-grid electrification in rural areas, energy efficiency initiatives, and electricity pricing policies. This policy brief seeks to show how Afghanistan can integrate gender and social concerns into energy projects to better address the country’s energy issues and achieve greater development impact. Chapter one gives introduction. Chapter two examines how energy can benefit men and women, emphasizing the gender-differentiated impacts of energy on human development and economic empowerment. Chapter three presents the socioeconomic status of Afghanistan and provides overviews on gender and the energy sector. Chapter four identifies several strategies for integrating gender and social considerations into the development and implementation of energy projects and programs in Afghanistan, including on-grid and off-grid electrification in rural areas, energy efficiency initiatives, and electricity pricing policies, with the aim of addressing current specific challenges.